Estudio de prefactibilidad para la instalación de una planta productora de shampoo en barra a base de las saponinas de la quinua - Romero Garcia, Cielomar Nicole (2022)
This project evaluates the economic, commercial, social, technological and environmental feasibility of installing a plant to produce a shampoo bar based on quinoa saponins as a natural surfactant, in order to meet the basic needs of hair care, through a product that takes advantage of quinoa waste and is environmentally friendly. A market study was conducted to determine the target population, which was defined as the group of people between 13 and 55 years of age, of socioeconomic levels A and B, in zones 6, 7 and 8 of Metropolitan Lima. In this way, the demand for the project was determined for a 5-year horizon, where, for the last year, a demand of 153,507 shampoo bars was obtained. In addition, a sample of the target population was surveyed and the selling price was determined at 30 soles. Then, a micro and macro location analysis was carried out, in which Villa el Salvador, Lima was determined as the district where the production plant will be located. Likewise, the optimum plant size was determined, for which the size-market was considered as a conclusive factor, calculated at 153,507 shampoo bars per year, an amount that exceeded the break-even point. In the engineering evaluation of the project, the process and machinery to be used were determined. The minimum production area was defined as 33.5 m2 and the total size of the facilities was considered to be 442 m2. In addition, an economic and financial evaluation of the project was carried out, which determined the total investment required at S/. 1,007,448, 30% of which is financed by a bank loan, with an NPV of 1,361,997 soles, an IRR of 65.09%, a benefit-cost ratio of 2.93, and a payback period of 2 years and 1 month. Finally, a social evaluation of the project was carried out, in which a total value added of 8,854,965 soles was obtained, indicating that the project is very beneficial to society.